The Holocaust in Three Generations : Families of Victims and Perpetrators of the Nazi Regime - Rosenthal, Gabriele 1954- (Verlag Barbara Budrich, 2010)
What form does the dialogue about the family past during the Nazi period take in families of those persecuted by the Nazi regime and in families of Nazi perpetrators and bystanders? What impact does the past of the first generation, and their own way of dealing with it have on the lives of their children and grandchildren?What are the differences between the dialogue about the family past and the Holocaust in families of Nazi perpetrators and in families of Holocaust survivors?This book examines these questions on the basis of selected case studies